Visual and Multimodal Urban Sociology : Exploring the Urban Everyday. - Pauwels, Luc (Research in urban sociology., 2023)
Presented over two volumes, Visual and Multimodal Urban Sociology A and B explore the use and potential of visual materials and methodologies that expand the level of analysis and ways of seeing in urban sociology.